2012
DOI: 10.1097/mnm.0b013e3283524220
|View full text |Cite
|
Sign up to set email alerts
|

90Y PET-based dosimetry after selective internal radiotherapy treatments

Abstract: According to our experience, 90Y PET is a promising and reliable technique for microsphere dose assessment and might pave the way for a patient-specific PET-based dosimetry after liver SIRT treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 23 publications
5
68
0
7
Order By: Relevance
“…HCC lesion dosimetry using rescaled VSVs (using MCNP) showed a mean D T of 139.3 Gy and D NL of 33.8 Gy [120] and this work noted a dose of 287 Gy to the tumour periphery, and 70…”
Section: Y Pet Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC lesion dosimetry using rescaled VSVs (using MCNP) showed a mean D T of 139.3 Gy and D NL of 33.8 Gy [120] and this work noted a dose of 287 Gy to the tumour periphery, and 70…”
Section: Y Pet Imagingmentioning
confidence: 99%
“…Adequate visualisation can be achieved with a 20 minute per bed scan [117,118] and sensitivities of 0.11 cps/MBq in patients [119], 0.577 and 1 cps/MBq in phantom [117,120] have been reported. In a recent study, the optimal contrast for hot and cold spheres in a phantom was obtained with LYSO crystals and TOF technology [121].…”
Section: Y Pet Imagingmentioning
confidence: 99%
“…Currently, SPECT-based quantitative imaging is more widely used than PET, as most therapeutic radionuclides emit photons suitable only for SPECT (Table 1). Recently, the possibility of performing PET quantitative imaging with 90 Y exploiting the extremely small β + branch ratio of this radionuclide has been proposed by several authors and applied both to SIRT treatments [9][10][11][12][13][14] and locoregional therapies that use 90 Y as therapeutic agent [15].…”
Section: Sequence Of Activity Measurements Within a Defined Tissue Vomentioning
confidence: 99%
“…Currently, SPECT-based quantitative imaging is more widely used than PET, as most therapeutic radionuclides emit photons suitable only for SPECT (Table 1). Recently, the possibility of performing PET quantitative imaging with 90 Y exploiting the extremely small β + branch ratio of this radionuclide has been proposed by several authors and applied both to SIRT treatments [9][10][11][12][13][14] and locoregional therapies that use 90 Y as therapeutic agent [15].To give absolute activity, the system must be calibrated and each image must be corrected for scatter, attenuation, partial volume effect, and dead time. While considerable work has been done in the application of correction techniques to both the filtered back-projection and iterative image reconstruction methodologies [16], there is no validated standard protocol, or any established methods for calibration or verification of system performance.…”
mentioning
confidence: 99%
“…Many studies have demonstrated the feasibility of using these PET images for patient-specific dosimetry (12,13). 90 Y is not an ideal radionuclide for PET imaging because of the low pair-production branching ratio.…”
mentioning
confidence: 99%